Gastrointestinal sarcoidosis presenting with malabsorption at an early age - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Sarcoidosis is a chronic multisystemic granulomatous disease that predominantly involves the thoracic lymph nodes and lungs and primarily occurs in young adults. Isolated extrapulmonary localization is uncommon in adults, and exceptionally rare in the pediatric age group. A 4-year-old male patient with chronic diarrhea and abdominal distention for the last 8 months is presented. Endoscopic biopsies, obtained during gastroscopy and colonoscopy, revealed noncaseating granulomas in all segments of the gastrointestinal tract. A noncaseating granuloma was also demonstrated in the liver biopsy. Granulomatous inflammation of both the gastrointestinal system and liver along with elevated serum angiotensin-converting enzyme were consistent with sarcoidosis. The peculiarity of our pediatric sarcoidosis was the involvement of whole gastrointestinal system, which is exceptionally rare in all age groups. Furthermore, this is the youngest case in the literature with gastrointestinal and hepatic sarcoidosis in the absence of pulmonary involvement at onset.
Keywords: Extra-pulmonary involvement; intestine; liver; pediatric sarcoidosis; stomach